2018
DOI: 10.1186/s13046-018-0818-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin-2 is a novel target of KRAS-ERK signaling involved in the development of pancreatic cancer

Abstract: BackgroundThe KRAS mutation is the driving force of pancreatic ductal adenocarcinoma (PDAC). Downstream effectors of KRAS signal pathways are crucial to the development of PDAC. The purpose of this study was to investigate the relationship between KRAS mutation and transgelin-2. Transgelin-2 is highly expressed in PDAC tissues compared with adjacent normal tissues. The underlying mechanism for upregulating transgelin-2 is largely unknown.MethodsExpression of transgelin-2 was analyzed by microarray data and qRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 58 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…Notably, a recent report regarding extracellular signal-regulated kinases (ERK) in KRAS -mutated PDAC, based on cell lines, pancreatic cancer organoids, and xenograft mouse-models, showed that ERK inhibition in cancer-associated stromal cells can suppress cancer-stromal interactions and PDAC metastatic potential [ 24 ]. Along these lines, Sun and colleagues, reported that inhibition of the phosphorylation of transgelin-2, a novel target of KRAS-ERK signaling, may be a potential therapeutic strategy for targeting PDAC with KRAS mutation, using PDAC cell lines, immunohistochemistry on PDAC tissues, and xenograft-mouse models [ 25 ]. Although promising, such findings are exploratory and still without a direct clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent report regarding extracellular signal-regulated kinases (ERK) in KRAS -mutated PDAC, based on cell lines, pancreatic cancer organoids, and xenograft mouse-models, showed that ERK inhibition in cancer-associated stromal cells can suppress cancer-stromal interactions and PDAC metastatic potential [ 24 ]. Along these lines, Sun and colleagues, reported that inhibition of the phosphorylation of transgelin-2, a novel target of KRAS-ERK signaling, may be a potential therapeutic strategy for targeting PDAC with KRAS mutation, using PDAC cell lines, immunohistochemistry on PDAC tissues, and xenograft-mouse models [ 25 ]. Although promising, such findings are exploratory and still without a direct clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Transgelin-2 expression is regulated at the transcriptional level by three major signaling pathways, including NF-κB, transforming growth factor β (TGFβ), and extracellular signal-regulated kinase (KRAS-ERK) pathways [10,30,31].…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…The third pathway modulating transgelin-2 expression is the epidermal growth factor receptor (EGFR) and KRAS-ERK signaling pathway [31]. The most relevant results of these studies are directly related to high transgelin-2 expression in pancreatic ductal adenocarcinoma (PDAC), representing the fourth leading cause of cancer-related death in the United States [35,36].…”
Section: Gene Expression Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgelin-2 is a microfilament-binding protein that protects microfilaments from cofilin-mediated depolymerization, and it is a tumor-suppressor [84][85][86][87][88]. This small protein is abundant in EVs, and in principle could be involved in stabilizing a significant amount of the actin as microfilaments.…”
Section: Stable Microfilaments In Evs?mentioning
confidence: 99%